DEVELOPING SPEAKING MATERIALS THROUGH TASK – BASED LEARNING FOR VOCATIONAL STUDENTS OF HOSPITALITY STUDY PROGRAM - Suchroni Panjaitan and Isli Iriani Indiah Pane (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
The objectives of this study are: (1) to know the existing English speaking materials for the students of hospitality study program, (2) to investigate the relevant English speaking materials for the students of hospitality study program, and (3) to develop appropriate English speaking materials through Task – Based Learning for the students of hospitality study program. This research was conducted at SMK Negeri 3 Tebing Tinggi. The research procedures of this study were Research and Development (R & D) through three phrases: 1) evaluation and need analysis, 2) course design, and 3) materials validation. The instruments used in this research were documentation sheet, interview and questionnaire. The data from evaluation and need analysis were analyzed in the descriptive analysis and the data from expert judgment results were using quantitative data analysis. The result of this study was a course book of speaking materials through task – based learning which consist of title, objective, let’s start, language in use, let’s practice, grammar in focus, and language reference. The task – based learning materials consist of three units, they are welcome to Grand Aston Hotel, talking on the phone, and what do they look like. Based on the experts’ judgement result, the score was 86.5 which belongs to good category based on Dirgeyasa (2011), since the range is (70 – 89).